Plastid genome data provide new insights into the dynamic evolution of the tribe Ampelopsideae (Vitaceae) - Lei Zhang; Ying Meng; Da Wang; Guan-Hao He; Jun-Ming Zhang; Jun Wen; Ze-Long Nie (BMC Genomics, 2024)
Abstract Background Ampelopsideae J. Wen & Z.L. Nie is a small-sized tribe of Vitaceae Juss., including ca. 47 species from four genera showing a disjunct distribution worldwide across all the continents except Antarctica. There are numerous species from the tribe that are commonly used as medicinal plants with immune-modulating, antimicrobial, and anti-hypertensive properties. The tribe is usually recognized into three clades, i.e., Ampelopsis Michx., Nekemias Raf., and the Southern Hemisphere clade. However, the relationships of the three clades differ greatly between the nuclear and the plastid topologies. There has been limited exploration of the chloroplast phylogenetic relationships within Ampelopsideae, and studies on the chloroplast genome structure of this tribe are only available for a few individuals. In this study, we aimed to investigate the evolutionary characteristics of plastid genomes of the tribe, including their genome structure and evolutionary insights. Results We sequenced, assembled, and annotated plastid genomes of 36 species from the tribe and related taxa in the family. Three main clades were recognized within Ampelopsideae, corresponding to Ampelopsis, Nekemias, and the Southern Hemisphere lineage, respectively, and all with 100% bootstrap supports. The genome sequences and content of the tribe are highly conserved. However, comparative analyses suggested that the plastomes of Nekemias demonstrate a contraction in the large single copy region and an expansion in the inverted repeat region, and possess a high number of forward and palindromic repeat sequences distinct from both Ampelopsis and the Southern Hemisphere taxa. Conclusions Our results highlighted plastome variations in genome length, expansion or contraction of the inverted repeat region, codon usage bias, and repeat sequences, are corresponding to the three lineages of the tribe, which probably faced with different environmental selection pressures and evolutionary history. This study provides valuable insights into understanding the evolutionary patterns of plastid genomes within the Ampelopsideae of Vitaceae.